Bifunctional RNA‐Targeting Deoxyribozyme Nanodevice as a Potential Theranostic Agent. Issue 16 (27th February 2020) - Spelkov, Aleksandr A.; Goncharova, Ekaterina A.; Savin, Artemii M.; Kolpashchikov, Dmitry M.
Abstract: Theranostic approaches rely on simultaneous diagnostic of a disease and its therapy. Here, we designed a DNA nanodevice, which can simultaneously report the presence of a specific RNA target through an increase in fluorescence and cleave it. High selectivity of RNA target recognition under near physiological conditions was achieved. The proposed approach can become a basis for the design of DNA nanomachines and robots for diagnostics and therapy of viral infections, cancer, and genetic disorders. Abstract : Two birds with one stone : A DNA association can complete both RNA‐cleaving (therapeutic) and RNA‐detecting (diagnostic) functions.